Effect of positive and negative corona discharge field on vigor of millet seeds - Wang, Jing (2021)
To investigate the effects of corona discharge field treatment of different electric field strength with the different polarities on the vigor of millet seeds, the positive and negative corona discharge fields generated with arc-shaped prick electrodes and plate electrodes are different for millet seeds respectively. The treatment voltage was (2 × n kV, n = 1, 2. . .10) and the time treated was 2 min. The results showed that after treatment by the corona discharge field, the germination potential, germination rate, germination index and vigor index of millet seeds increased to different degrees compared with the control. The optimal treatment voltages of the positive and negative corona discharge field were 12 kV. Under the optimal treatment voltage, the germination indexes (germination potential, germination rate, germination index, vigor index) of millet seeds were significantly different from the control (p <; 0.01), and the millet seeds treated by the positive corona discharge field compared with the control group, the germination potential, germination rate, germination index and vigor index increased by 21.2%, 23.0%, 19.9% and 23.2% respectively. The germination indexes of the millet seeds treated by the negative corona discharge field increased by 29.1%, 28.5%, 26.9% and 32.1%. It was also found that under the same treatment voltage, the electrical conductivity of the leachates of the millet seed treated with the negative corona discharge field was lower than that of the positive, which indicated that the negative corona discharge field would repair the cell membrane more effectively. According to various indicators, it can be concluded that the negative corona discharge field treatment was better than the positive.